2012
DOI: 10.1177/0194599811434383
|View full text |Cite
|
Sign up to set email alerts
|

Stratifying the Risk of Venous Thromboembolism in Otolaryngology

Abstract: Objective The consequences of perioperative venous thromboembolism (VTE) are devastating; identifying patients at risk is an essential step in reducing morbidity and mortality. The utility of perioperative VTE risk assessment in otolaryngology is unknown. This study was designed to risk-stratify a diverse population of otolaryngology patients for VTE events. Study Design Retrospective cohort study. Setting Single-institution academic tertiary care medical center. Subjects and Methods Adult patients prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
148
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 142 publications
(156 citation statements)
references
References 31 publications
6
148
0
2
Order By: Relevance
“…[9][10][11]28 However, the model requires yes/no answers to 40 risk factor questions, which may limit physician compliance with completion. 13 The Rogers score was published in 2007 after being developed using rigorous statistical methods based on data from the Veterans Administration Patient Safety Study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11]28 However, the model requires yes/no answers to 40 risk factor questions, which may limit physician compliance with completion. 13 The Rogers score was published in 2007 after being developed using rigorous statistical methods based on data from the Veterans Administration Patient Safety Study.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that a 10-to 20-fold difference in VTE risk exists among the overall surgical population. [8][9][10][11] The American College of Chest Physicians (ACCP) guidelines on VTE prevention have long been the standard for conceptualizing VTE risk. 12 The most recent ACCP guidelines, Antithrombotic Therapy and Prevention A nnually, 12 million hospitalized patients are at risk of VTE, which includes DVT and pulmonary embolus (PE).…”
mentioning
confidence: 99%
“…8 The literature describes several methods of stratifying otolaryngology patients by risk for VTE. 8,10,11 One method is the Caprini risk assessment model. [10][11][12] This model is used to determine each patient's individual risk for VTE.…”
mentioning
confidence: 99%
“…8,10,11 One method is the Caprini risk assessment model. [10][11][12] This model is used to determine each patient's individual risk for VTE. The Caprini model uses a point scoring system; the relative scores for each patient's risk factors are summed to produce a cumulative risk score that defines the patient's risk level and associated prophylaxis regimen.…”
mentioning
confidence: 99%
“…Модель J. Caprini прошла удачную ретроспек тивную валидацию у пациентов общехирургическо го, сосудистого и урологического профиля, боль ных, подвергшихся пластической и реконструктив ной хирургии, перенесших операции на ЛОР органах, а также у пациентов из отделений ОРИТ и получила мировое признание [104][105][106][107][108]. Между тем до сих пор модель J. Caprini была ограничена выде лением гетерогенной группы высокого риска по аналогии с традиционными оценочными система ми.…”
Section: флебология 1 2015unclassified